2016
DOI: 10.1111/his.12992
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E and NRASQ61L/Q61R mutation analysis in metastatic melanoma using immunohistochemistry: a study of 754 cases highlighting potential pitfalls and guidelines for interpretation and reporting

Abstract: The use of IHC is a fast, efficient and cost-effective method to identify single specific mutations in melanoma patients. BRAF(V600E) and NRAS(Q61R) antibodies have high sensitivity and specificity; however, the NRAS(Q61L) antibody appears less sensitive. IHC can help to facilitate the timely, appropriate selection and treatment of metastatic melanoma patients with targeted therapies. Detection of melanoma-associated mutations by IHC may also provide evidence for a diagnosis of melanoma in metastatic undiffere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…It has been established that immunohistochemical detection of mutant BRAF V600 (VE1) protein can be used in clinical practice as a first screening test for BRAF mutations. Several authors (25)(26)(27)(28) have confirmed the correlation between immunohistochemical staining, using an anti-BRAF V600E (VE1) primary antibody and sequencing analysis. The authors highlighted that BRAF V600E (VE1) antibody is a reliable, highly specific antibody for the detection of mutated BRAF V600E protein.…”
Section: J Oral Pathol Medmentioning
confidence: 88%
“…It has been established that immunohistochemical detection of mutant BRAF V600 (VE1) protein can be used in clinical practice as a first screening test for BRAF mutations. Several authors (25)(26)(27)(28) have confirmed the correlation between immunohistochemical staining, using an anti-BRAF V600E (VE1) primary antibody and sequencing analysis. The authors highlighted that BRAF V600E (VE1) antibody is a reliable, highly specific antibody for the detection of mutated BRAF V600E protein.…”
Section: J Oral Pathol Medmentioning
confidence: 88%
“…40,41 Several authors confirmed that anti-BRAF V600E (VE1) antibody provides high reliability and specificity in the detection of mutated BRAF V600E protein. 42 Recently, some new molecular assays for BRAF mutations have become available. These are fully automated molecular diagnostic systems for quantitative allele-specific RT-PCR-based analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry can serve as a quick screen, with excellent sensitivity for the BRAF V600E mutation. If immunohistochemistry is negative, alternative forms of testing are required to screen for other treatable mutations in BRAF (such as V600K, present in 10–20 per cent of the BRAF ‐mutant melanoma population) and other genes.…”
Section: Genomic Testing To Guide Treatment Of Metastatic Diseasementioning
confidence: 99%